The Nox1/4 Dual Inhibitor GKT137831 or Nox4 Knockdown Inhibits Angiotensin‐II‐Induced Adult Mouse Cardiac Fibroblast Proliferation and Migration. AT1 Physically Associates With Nox4. Issue 5 (19th October 2015) - Somanna, Naveen K.; Valente, Anthony J.; Krenz, Maike; Fay, William P.; Delafontaine, Patrice; Chandrasekar, Bysani
Abstract : Both oxidative stress and inflammation contribute to chronic hypertension‐induced myocardial fibrosis and adverse cardiac remodeling. Here we investigated whether angiotensin (Ang)‐II‐induced fibroblast proliferation and migration are NADPH oxidase (Nox) 4/ROS and IL‐18 dependent. Our results show that the potent induction of mouse cardiac fibroblast (CF) proliferation and migration by Ang‐II is markedly attenuated by Nox4 knockdown and the Nox inhibitor DPI. Further, Nox4 knockdown and DPI pre‐treatment attenuated Ang‐II‐induced IL‐18, IL‐18Rα and collagen expression, and MMP9 and LOX activation. While neutralization of IL‐18 blunted Ang‐II‐induced CF proliferation and migration, knockdown of MMP9 attenuated CF migration. The antioxidant NAC and the cell‐permeable SOD mimetics Tempol, MnTBAP, and MnTMPyP attenuated oxidative stress and inhibited CF proliferation and migration. The Nox1/Nox4 dual inhibitor GKT137831 also blunted Ang‐II‐induced H2 O2 production and CF proliferation and migration. Further, AT1 bound Nox4, and Ang‐II enhanced their physical association. Notably, GKT137831 attnuated the AT1/Nox4 interaction. These results indicate that Ang‐II induces CF proliferation and migration in part via Nox4/ROS‐dependent IL‐18 induction and MMP9 activation, and may involve AT1/Nox4 physical association. Thus, either (i) neutralizing IL‐18, (ii) blocking AT1/Nox4 interaction or (iii) use of the Nox1/Nox4 inhibitor GKT137831 may have therapeutic potential in chronic hypertension‐induced adverse cardiac remodeling. J. Cell. Physiol. 231: 1130–1141, 2016. © 2015 Wiley Periodicals, Inc.